Reconstruction of acetabular defects with porous tantalum shells and augments in revision total hip arthroplasty at ten-year follow-up. (March 2019) - Löchel, J.; Janz, V.; Hipfl, C.; Perka, C.; Wassilew, G. I.
Abstract : Aims: The use of trabecular metal (TM) shells supported by augments has provided good mid-term results after revision total hip arthroplasty (THA) in patients with a bony defect of the acetabulum. The aim of this study was to assess the long-term implant survivorship and radiological and clinical outcomes after acetabular revision using this technique. Patients and Methods: Between 2006 and 2010, 60 patients (62 hips) underwent acetabular revision using a combination of a TM shell and augment. A total of 51 patients (53 hips) had complete follow-up at a minimum of seven years and were included in the study. Of these patients, 15 were men (29.4%) and 36 were women (70.6%). Their mean age at the time of revision THA was 64.6 years (28 to 85). Three patients (5.2%) had a Paprosky IIA defect, 13 (24.5%) had a type IIB defect, six (11.3%) had a type IIC defect, 22 (41.5%) had a type IIIA defect, and nine (17%) had a type IIIB defect. Five patients (9.4%) also had pelvic discontinuity. Results: The overall survival of the acetabular component at a mean of ten years postoperatively was 92.5%. Three hips (5.6%) required further revision due to aseptic loosening, and one (1.9%) required revision for infection. Three hips with aseptic loosening failed, due to insufficient screw fixation of the shell in two and pelvic discontinuity in one. The mean Harris Hip Score improved significantly from 55 (35 to 68) preoperatively to 81 points (68 to 99) at the latest follow-up (p < 0.001). Conclusion: The reconstruction of acetabular defects with TM shells and augments showed excellent long-term results. Supplementary screw fixation of the shell should be performed in every patient. Alternative techniques should be considered to address pelvic disconinuity. Cite this article: Bone Joint J 2019;101-B:311–316.